2003
DOI: 10.1007/bf02492414
|View full text |Cite
|
Sign up to set email alerts
|

Use of OPLC to study the biological activity of organic compounds

Abstract: Solute capacity factors in pure water, log k,,,,, determined by the new method based on Ogcik's equation, are proposed as descriptors of the biological activity of some benzamides. Values of log k,,,, determined by the new method and by parabolic extrapolation were compared with the minimum inhibitory concentration (M/C) of the compounds against six different dermatophytes, and correlations bel',,veen log k,,,, and log (1//VIIC) values of the same substances were analysed. For all the dermatophytes and all the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…In the method the values of log k org, log k and x org are known (experimentally evaluated) and log k w parameter is determined by numerical fitting to equation 14 to obtain the linearity between the left term denoted as G and x org . We tested numerical method for different groups of substances, using various mobile and stationary phases by thin-layer, overpressured-layer and column reversed-phase chromatography techniques [Janicka, 2003;Janicka et al, 2006;Janicka, 2007) and numerical log k w parameters proved to be very good lipophylicity descriptors linear correlated to experimental and calculated log P values and moreover, in contrary to extrapolated, almost independent of the range of organic modifier concentration in the effluent.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…In the method the values of log k org, log k and x org are known (experimentally evaluated) and log k w parameter is determined by numerical fitting to equation 14 to obtain the linearity between the left term denoted as G and x org . We tested numerical method for different groups of substances, using various mobile and stationary phases by thin-layer, overpressured-layer and column reversed-phase chromatography techniques [Janicka, 2003;Janicka et al, 2006;Janicka, 2007) and numerical log k w parameters proved to be very good lipophylicity descriptors linear correlated to experimental and calculated log P values and moreover, in contrary to extrapolated, almost independent of the range of organic modifier concentration in the effluent.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…[1,2] Numerous research papers that have been published during the last years confirmed that the lipophilicity has significant impact on toxicity of organic compounds including pesticides and also on their bioaccumulation. [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] The relationship between bioaccumulation coefficient (K d ) of these compounds and partition coefficient (designated, e.g., as K ow or logP) determined by the use of proper method (theoretical or experimental) shows that described lipophilicity may correlate with bioaccumulation profile of pesticides according to Eq. (1):…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14][15][16] However, the log k w values determined by these methods differ in dependence on the type of extrapolation function, the concentration range of the organic modifier for which chromatographic measurements were made, and the type of organic modifier. One of the alternative calculation methods of this parameter is the numerical method [17][18][19][20] based on the linear form of the Ościk's equation, [21] which was also used in this study.…”
Section: Introductionmentioning
confidence: 99%